Providing a good start. Concerns of beginning secondary school teachers and support provided. Issue 2 (14th March 2020) - Aarts, Rian; Kools, Quinta; Schildwacht, Rita
ABSTRACT: The first years in the teaching profession are often a challenge and most beginning teachers struggle with concerns. To support beginning teachers, induction programmes have been developed which should lead to an acceleration of growth in teaching skills and prevent drop-out. In this study, we explore the concerns of beginning teachers in secondary education and the support provided. Nineteen teachers in their first and 16 teachers in their second year of employment were questioned. Results show that first year teachers are mainly concerned about their lessons, but later the focus is moving inward to their professional teacher role and outward to the school organisation. The concerns of beginning teachers are being dealt with in a variety of support activities without a direct link between the two. Nevertheless, teachers seem to be able to cope if provided with sufficient support, a coach they can relate to and possibilities for informal feedback.